Spirituality across Disciplines: Research and Practice: - de Souza, Marian; Bone, Jane; Watson, Jacqueline (Springer International Publishing : Imprint: Springer, 2016)
This book collects multiple disciplinary voices which explore current research and perspectives to discuss how spirituality is understood, interpreted and applied in a range of contexts. It addresses spirituality in combination with such topics as Christian mysticism, childhood and adolescent education, midwifery, and sustainability. It links spirituality to a variety of disciplines, including cognitive neuroscience, sociology, and psychology. Finally, it discusses the application of spirituality within the context of social work, teaching, health care, and occupational therapy. A final chapter provides an analytical discussion of the different voices that appear in the book and offers a holistic description of spirituality which has the potential to bring some unity to the meaning, expression and practice of spirituality across a variety of disciplines as well as across cultural, religious and secular worldviews. "A strength of the book is that each chapter is characterized by a fearless confronting of oppositional perspectives and use of the latest research in addressing them. The book takes the difficult topic of spirituality into almost every nook and cranny of personal and professional life. There is a persistent grasping of the contentiousness of the topic, together with addressing counter positions and utilizing updated research across a range of fields in doing this. The opening and closing chapters serve as book ends that keep the whole volume together." Terence Lovat, The University of Newcastle, Australia "The interdisciplinary nature of the work is by far the strongest aspect of this volume. It has the potential to contribute to a dialogue between different professions and disciplines. This prospective publication promises to promote a more holistic approach to the study of spirituality. This volume takes into consideration a wide variety of issues. The way the editors have structured the sequence of chapters contributes to facilitate any possible dialogue between the different areas." Adrian-Mario Gellel, University of Malta, Malta.